2013
DOI: 10.1371/journal.pone.0057475
|View full text |Cite|
|
Sign up to set email alerts
|

Metabolic Factors Associated with Risk of Renal Cell Carcinoma

Abstract: Previous studies have shown that obesity and hypertension are associated with increased risk of renal cell carcinoma (RCC), but less is known about the association to other metabolic factors. In the Metabolic Syndrome and Cancer project (Me-Can) data on body mass index (BMI, kg/m2), blood pressure, and circulating levels of glucose, cholesterol, and triglycerides were collected from 560,388 men and women in cohorts from Norway, Austria, and Sweden. By use of Cox proportional hazard models, hazard ratios (HR) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 36 publications
(50 reference statements)
3
67
0
1
Order By: Relevance
“…Those metabolic factors were high levels of BMI, BP, glucose, TG among men and BMI among women. However, the authors observed no interaction between the risk factors and RCC (Haggstrom et al, 2013). In the present study, we investigated the relationship between the risk of RCC and MetS which is referred to a constellation of interrelated metabolic risk factors.…”
Section: Discussionmentioning
confidence: 90%
“…Those metabolic factors were high levels of BMI, BP, glucose, TG among men and BMI among women. However, the authors observed no interaction between the risk factors and RCC (Haggstrom et al, 2013). In the present study, we investigated the relationship between the risk of RCC and MetS which is referred to a constellation of interrelated metabolic risk factors.…”
Section: Discussionmentioning
confidence: 90%
“… study. In another European cohort study, the link between triglyceride and RCC hazard was only seen in men but not in women . To our knowledge, little research has been reported on the role of LDL in carcinogenesis, especially for RCC.…”
Section: Discussionmentioning
confidence: 86%
“…5 Smoking, obesity and hypertension are high risk factors for this condition. 6 NSAID is another high risk factor. 7 Immediate relatives of people with RCC have 2-4 old increased risk of developing the disease.…”
Section: Discussionmentioning
confidence: 99%